The association of urotensin II with arterial stiffness and atherosclerosis in patients with autosomal dominant polycystic kidney disease (Annals of Medical Research, 2021)
Aim: Cardiovascular events are associated with increased mortality in patients with autosomal dominant polycystic kidney disease (ADPKD). Urotensin II (UT II) is the most potent vasoconstrictor peptide. The aim of the study was to investigate the relationship between UT II and arterial stiffness (AS) and atherosclerosis in ADPKD patients.Material and Methods: This cross-sectional study was conducted on 55 ADPKD patients with a mean age of 50 ± 14.4years. The presence of AS was determined with brachial-ankle pulse wave velocity (baPWV) and the presence of atherosclerosis was determined with carotid artery intima-media thickness (CA-IMT). Plasma UT II levels were determined by enzyme-linked immunosorbent assay.Results: Mean log10 UT II was 0.92±0.16 ng/mL. Mean baPWV and CA-IMT were 7.65±1.5 m/sec and 0.63±0.13 mm, respectively. Log10 UT II (p=0.009), baPWV (p 0.001) and CA-IMT (p=0.001) were high in patients compared to healthy individuals. There was an independent relationship between log10 UT II and creatinine (p=0.044) and spot urine protein-creatinine ratio (UPCR) (p=0.026) in multiple regression analysis. There was no relationship between log10 UT II and baPWV and CA-IMT.Conclusion: High plasma UT II levels were observed in ADPKD patients compared to healthy individuals. There was a relationship between UT II and kidney dysfunction and proteinuria. There was no relationship between UT II and AS and atherosclerosis.Keywords: Autosomal dominant polycystic kidney disease; arterial stiffness; atherosclerosis; urotensin ΙΙ.